THE INFLUENCE OF UNDERSTANDING THE VALUES OF PANCASILA ON LEGAL AWARENESS: A STUDY ON UNIVERSITY STUDENTS - Nazwa Rahma Fitri; Chelsie Nayla Shaqi; Nadiyah Putri Budiani; Abbad Dzorif; Fadhillah Mubarok Siregar (Academic Solution Publisher, 2024)
This study aims to analyze the influence of understanding Pancasila values on legal awareness among university students. Using a quantitative descriptive method, the research involved 28 student respondents selected through purposive sampling technique. Data was collected using a 5-point Likert scale questionnaire consisting of 15 statements covering dimensions of understanding Pancasila values and legal awareness. The results showed a positive correlation between understanding Pancasila values and students' legal awareness, where 78.6% of respondents demonstrated good understanding of Pancasila values and 60.7% complied with regulations based on awareness. However, gaps were found in practical implementation, particularly in aspects of rule enforcement by students, with only 28.6% willing to reprimand violations and 32.1% reporting academic dishonesty. The research recommends developing integrated programs for strengthening Pancasila values internalization, building safe violation reporting systems, social courage training, strengthening role models, and periodic evaluation of Pancasila-based legal awareness programs